STRATEGI EFEKTIF DINAS TENAGA KERJA DAN TRANSMIGRASI DALAM MENGURANGI ANGKA PENGANGGURAN - Muhammad Haryono; Maulana (Jurnal Integritas Serasan Sekundang, 2023)
This study aims to describe the strategy to reduce open unemployment in the Muara Enim Regency area. This study uses a descriptive qualitative approach. Technical analysis of data is done by collecting data, presenting data, reducing data and drawing conclusions. The results showed that the implementation of the strategy of the Department of Manpower and Transmigration in reducing unemployment in Muara Enim Regency was aimed at reducing unemployment, especially open unemployment in the Muara Enim Regency area. The inhibiting factor in reducing unemployment is public knowledge about the importance ofcompetence (hard skills and soft skills) in order to compete in the world of work, as well as the importance of company awareness to prioritize hiring workers from residents of Muara Enim Regency who already have competence and are certified according to company needs. The supporting factor in reducing the unemployment rate in Muara Enim Regency is the commitment of the Head of Manpower and Transmigration Office of Muara Enim Regency and his staff to improve the performance of existing programs and activities so as to create innovations in the education and training sector as well as staff placement